2018
DOI: 10.1002/jcph.1329
|View full text |Cite
|
Sign up to set email alerts
|

Negative Association of Proton Pump Inhibitors With Subsequent Development of Breast Cancer: A Nationwide Population‐Based Study

Abstract: Although current evidence suggests potential antitumor activity of proton pump inhibitors (PPIs), there is no population-based evidence of an association between PPI use and subsequent breast cancer risks. We used an observational case-control study to examine the association between prior PPI use and breast cancer occurrence. Additional analysis examined dose-response and age-stratified associations of PPIs with breast cancer. This study used data from the Taiwan National Health Insurance Research Dataset. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…NHE1 levels are higher in BC tissue than in normal breast tissue, and also in resistant BC cells than in sensitive cells, in a similar fashion to other PTs [ 4 , 10 , 51 , 55 , 56 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Apart from NHE1 overexpression, carbonic anhydrases also have an important role in the pathogenesis of BC, like V-ATPase proton pumps, the Na + –HCO 3 − cotransporter (SLC4A7,NBCn1, MCTs, hypoxia and hypoxia-inducing factor 1 (HIF-1) [ 75 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The supporting
confidence: 59%
See 1 more Smart Citation
“…NHE1 levels are higher in BC tissue than in normal breast tissue, and also in resistant BC cells than in sensitive cells, in a similar fashion to other PTs [ 4 , 10 , 51 , 55 , 56 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Apart from NHE1 overexpression, carbonic anhydrases also have an important role in the pathogenesis of BC, like V-ATPase proton pumps, the Na + –HCO 3 − cotransporter (SLC4A7,NBCn1, MCTs, hypoxia and hypoxia-inducing factor 1 (HIF-1) [ 75 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The supporting
confidence: 59%
“…Moreover, there is a significant increase in the survival of women who continue their PPI therapy after the completion of chemotherapy for BC [ 224 ]. On the other hand, women receiving PPI treatment for non-cancerous diseases have a reduced risk of developing BC [ 71 , 225 ]. Intermittent high dose PPI also improves MDR in metastatic BC [ 223 ].…”
Section: Towards An Etiology-based and H + -Relmentioning
confidence: 99%
“…More recent reports have shown that women affected by medical conditions suitable for PPI treatment, e.g. peptic diseases, have a reduced risk for developing BC [52,197]. Both studies were performed in a very large cohort of patients with very convincing results.…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%
“…d) pH, proton transporters (PTs), proton pumps (PPs) and their inhibitors (PTIs and PPIs) [14,32,36,38,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. e) pH and voltage gated sodium channels (VGSC) [56][57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment modalities have been adopted to interfere with glycolysis, e.g., some pharmacological agents used to treat cancer via restoration of the mitochondrial function to support programmed cell death (apoptosis); some of these agents include Proton Pump Inhibitors (PPIs), Hydroxycitrate, NaHCO 3 , Lipoic acid, and could be extended to use some of the natural extracts, e.g., Fermented wheat germ extract FWGE [14,[57][58][59][60][61][62].…”
Section: Tumor Metabolismmentioning
confidence: 99%